Answer:
f(n)=n²-3
Step-by-step explanation:
In the sequence:
![-2,1,6,13,22,...](https://img.qammunity.org/2023/formulas/mathematics/college/wu6lwtsu80cau7kl7pfqlk7grc7j3w7e6u.png)
First, we find the difference between the terms.
![\begin{gathered} 1-(-2)=3 \\ 6-1=5 \\ 13-6=7 \\ 22-13=9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lybk6s0h0o0ihd2te7sbee3ic7ky6zystm.png)
It is observed that the difference between successive terms is the addition of consecutive odd numbers.
This is an example of a quadratic sequence.
The general form of a quadratic sequence is:
![\begin{gathered} f(n)=an^2+bn+c \\ f(1)=-2 \\ \implies a+b+c=-2 \\ f(2)=1 \\ \implies4a+2b+c=1 \\ f(3)=6 \\ \implies9a+3b+c=6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dk516keqyoz5ds2ljn57l6lvsntvlwg1dk.png)
If we solve the system of equations:
![\begin{gathered} a+b+c=-2 \\ 4a+2b+c=1 \\ 9a+3b+c=6 \\ a=1,b=0,c=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pw2e8n6oe77egau7og20jebjffaxiudi5w.png)
The explicit expression for this sequence is:
![f(n)=n^2-3](https://img.qammunity.org/2023/formulas/mathematics/college/jpxe87hdaszw9qgydujhsxvk22861jeil8.png)